2007
DOI: 10.1039/b708236c
|View full text |Cite
|
Sign up to set email alerts
|

Development of a microfluidic biochip for online monitoring of fungal biofilm dynamics

Abstract: Microfabricated biochips are developed to continuously monitor cell population dynamics in a non-invasive manner. In the presented work we describe the novel combination of contact-less dielectric microsensors and microfluidics to promote biofilm formation for quantitative cell analysis. The cell chip consists of a polymeric fluidic (PDMS) system bonded to a glass wafer containing the electrodes while temperature and fluid flow are controlled by external heating and pumping stations. The high-density interdigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 42 publications
0
52
0
Order By: Relevance
“…Biofilm growth rates have been determined by various techniques, such as fluorescence in situ hybridization (FISH) (12,31), measuring the incorporation of radioactive substances like [ 3 H]thymidine and 32 P (8, 9), microscopy (3,13,17), measuring the total increase in biofilm mass (both cells and extracellular polymeric substances) (24,28), colorimetric 2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenyl-amino)carbonyl]-2H-tetrazolium hydroxide (XTT) assays (26), or measurement of amide II bands, as determined by attenuated total reflectanceFourier transform infrared spectroscopy (6). Some of the above-mentioned techniques suffer the drawback that the bio-films have to be sacrificed with sampling or that the measured increases do not distinguish between live and dead matter in the biofilm (i.e., increases measured might not represent an accurate increase in viable cell numbers).…”
mentioning
confidence: 99%
“…Biofilm growth rates have been determined by various techniques, such as fluorescence in situ hybridization (FISH) (12,31), measuring the incorporation of radioactive substances like [ 3 H]thymidine and 32 P (8, 9), microscopy (3,13,17), measuring the total increase in biofilm mass (both cells and extracellular polymeric substances) (24,28), colorimetric 2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenyl-amino)carbonyl]-2H-tetrazolium hydroxide (XTT) assays (26), or measurement of amide II bands, as determined by attenuated total reflectanceFourier transform infrared spectroscopy (6). Some of the above-mentioned techniques suffer the drawback that the bio-films have to be sacrificed with sampling or that the measured increases do not distinguish between live and dead matter in the biofilm (i.e., increases measured might not represent an accurate increase in viable cell numbers).…”
mentioning
confidence: 99%
“…In brief, a nonexhaustive list of techniques that deal only with online monitoring increase (whether of biotic or abiotic origin) and the decrease of biofilms includes quartz crystal microbalances (48), large area photometry (3,33), electrical capacitance (31), fiber optical devices (49), differential turbidity measurement devices (20), microfluidic biochips (39), optical coherence tomography (13), pressure drop or friction resistance (24), and heat transfer resistance (28). Techniques that provide information about the physical structure and chemical properties of biofilms are nuclear magnetic resonance (44), attenuated total reflectance-Fourier transform infrared spectroscopy (7), and photoacoustic spectroscopy (43).…”
mentioning
confidence: 99%
“…A microfluidic device was used to control and monitor the environment of biofilms caused by Candida albicans, the organism responsible for candidiasis. A device with dielectric sensors was created to measure the real-time response of C. albicans biofilms to different shear stresses and antibiotic concentrations 25 . The findings suggested that an increased shear stress led to considerable changes in the biofilm formation patterns, whereas the addition of an antibioticamphotericin B resulted in two distinct forms of dynamic behaviour of the biofilm.…”
Section: Microbiology and Cell Biologymentioning
confidence: 99%